THE INFLUENCE OF CLARITY OF BUDGET TARGETS, GOVERNMENT ACCOUNTING STANDARDS, AND REPORTING SYSTEMS ON THE PERFORMANCE ACCOUNTABILITY OF SUMENEP GOVERNMENT INSTITUTIONS - Fidya Istiqfarini; Tituk Diah Widajantie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine and prove the effect of clarity on budget targets, government accounting standards, and reporting systems on the performance accountability of government agencies the in Sumenep Regency. The method used in this research is a quantitative method. The population in this study was 51 Regional Apparatus Organizations in Sumenep Regency. The sample of this research is 15 regional offices and 5 regional agencies with a total of 60 respondents. The data analysis technique used is using Partial Least Square (PLS) with the software SmartPLS 3.0. The results of this study indicate that the clarity of budget targets has an insignificant positive effect on accountability for government agency performance, while government accounting standards and reporting systems have a significant positive effect on accountability for government agency performance.